Understanding the mechanism underlying the anti-inflammatory effect of dietary flavonoids on IBD: a focus on gut microbiota and its metabolites involved in SCFA, bile acid, tryptophan and lipopolysaccharides - Huihui Xiong; Hui Chen; Lingli Chen; Kehui Ouyang; Suyun Lin; Wenjun Wang (Food Science and Human Wellness)
Inflammatory bowel disease (IBD) is a chronic gastrointestinal disease with a high incidence. Treatment for IBD includes medications and diet, and common anti-inflammatory medications have limitations like drug resistance and serious adverse effects. Accumulating evidence has demonstrated that dietary flavonoids exhibit an alleviative effect on IBD by influencing gut microbiota. The microbiota-derived metabolites also regulate IBD and maintain intestinal homeostasis. In this review, we investigate the therapeutic effect of gut microbiota and metabolites on IBD by intestinal immune and intestinal barrier function. We demonstrate the underlying mechanism of dietary flavonoids as an anti-inflammatory molecule alleviating IBD by regulating gut microbiota, short chain fatty acid (SCFA), bile acid (BA), tryptophan (Trp) metabolism and lipopolysaccharides (LPS)-toll-like receptor 4 (TLR4) signaling pathway. Based on structural differences of flavonoids, we summarize the recent research progress on the role of different dietary flavonoids in alleviating IBD by gut microbiota and metabolites in animal and clinical trials. This review indicates that dietary flavonoids targeting gut microbiota and metabolites provide a promising strategy for the treatment of inflammation and novel insights into the management of IBD.